Gender‐Specific Risk Factors for Peripheral Artery Disease in a Voluntary Screening Population. Issue 2 (13th March 2014) - Hiramoto, Jade S.; Katz, Ronit; Weisman, Steven; Conte, Michael
Abstract : Background: Women have high rates of peripheral artery disease (PAD) despite fewer cardiovascular disease (CVD) risk factors, compared to men. We sought to determine the gender‐specific prevalence of low ankle brachial index (ABI) and the relationship to C‐reactive protein (CRP) levels and CVD risk factors in the Life Line Screening population. Methods and Results: Between April 2005 and August 2011, 133 750 women and 71 996 men had ABI and CRP measured at a Life Line Screening Center. Women were slightly older than men, whereas men were more likely to be current smokers, have diabetes mellitus (DM), and coronary artery disease (CAD) ( P <0.001 for each). Women were more likely to have ABI≤1.0, compared to men (26.6% versus 14.4%, respectively; P <0.001), as well as ABI≤0.9 (4.1% women versus 2.6% men; P <0.001). Women had higher median CRP levels (1.94 mg/L; interquartile range [IQR], 0.89, 4.44 mg/L), compared to men (1.35 mg/L; IQR, 0.73, 2.80 mg/L; P <0.001). Men and women shared similar risk factors for ABI≤0.9, including older age, black race, smoking, DM, hypertension, hypercholesterolemia, CAD, and elevated CRP levels. In an adjusted model, there were significant interactions between gender and age ( P <0.001), CRP ( P <0.001), CAD ( P =0.03), and DM ( P =0.06) with ABI as the outcome. The associations between age, CRP, CAD, and DM with ABI≤0.9 were stronger in men than in women. Conclusions: Women participating in the Life Line Screening had higher CRP levels and a higher prevalence of PAD, compared to men. Neither higher CRP levels nor conventional CVD risk factors explained the excess prevalence of PAD in women.